Efektivitas Penggunaan Media Augmented Reality (AR) Dalam Meningkatkan Hasil Belajar Matematika Kelas IV Madrasah Ibtidaiyah Darul Huda - Ayu Endita Irawan; Azizatul Alif Syafriza; Yuninda Dwindiyantik (Sangkalemo : The Elementary School Teacher Education Journal, 2026)
This study was conducted to test the effectiveness of the use of Augmented Reality (AR) media in improving the learning outcomes of mathematics students in grade IV of MI Darul Huda. This study uses a quantitative method with a quasi-experimental type. This type of pseudo-experimental design involves two groups, namely the experimental group and the control group. The data collection techniques and instruments used are tests and documentation. The data analysis techniques in this study are descriptive analysis, normality and homogeneity tests, for the data analysis technique of the hypothesis test in this study is the Independent Sample T-test. The results of the study showed that the Independent Sample T-test had a significant difference in the experimental class that used Augmented Reality (AR) media and the control class that used Canva media. The results of the Independent Sample T-test showed a sig (2-tailed) value of 0.000 < 0.05 which means that the independent variable over the hypothesis dependent variable is acceptable. The average obtained in the experimental class was 87.14, while the average obtained in the control class was 63, meaning that the use of Augmented Reality (AR) media had a higher average value. This means that the use of Augmented Reality (AR) media is effectively used in improving the mathematics learning outcomes of fourth grade students of MI Darul Huda.